Treatment of Laryngeal Granulomas - Garcia Martins, Regina Helena [UNESP]; Dias, Norimar Hernandes [UNESP]; Paiva Soares, Carlos Segundo [UNESP]; Joia Gramuglia, Andrea Cristina [UNESP] (Georg Thieme Verlag Kg, 2019)
Introduction Laryngeal granulomas are benign, recurrent lesions of many causes (reflux, voice abuse, intubation, and idiopathic), which renders its treatment difficult. Objective To describe our experience in the treatment of laryngeal granulomas. Methods From 16 medical records of the patients with laryngeal granulomas seen between 2010 and 2017 in a university hospital, the following data were analyzed: age, gender, vocal and gastroesophageal symptoms, vocal overuse, intubation, treatments, videolaryngoscopy before and after the treatment. Results Gender: female, 10; male, 6. Age: between 20 and 60 years old (11). Etiology of the granulomas: intubation (9), reflux (4), idiopathic (3). The initial treatments adopted in all cases were: inhaled beclomethasone dipropionate 100 mu g 12/12 hours (1 month), proton pump inhibitor, omeprazole 40 mg/day (2 months), and dietary and voice education. After this period, 10 patients (7 postintubation, 3 idiopathic) were submitted to surgery, since no improvements in the symptoms or in the lesions were seen. Of these, two recurred, requiring a second surgery, one of which recurred six times and received botulinum toxin A. Only one patient with granulomas due to laryngopharyngeal reflux presented no improvement in the symptoms nor in the lesion after the pharmacological treatment and had been submitted to microsurgery. All of the other patients with reflux granulomas were successfully treated with the drug treatment, and the longest treatment time for complete remission of the symptoms and of the lesions was 9 months. Conclusions In laryngeal granulomas caused by reflux, treatment with inhaled steroids and proton pump inhibitors proved to be effective, although prolonged. In postintubation and idiopathic granulomas, surgery was the best treatment.
Keywords: granuloma; larynx; intubation; treatment